Impact of Long-Term Growth Hormone Replacement Therapy on Metabolic and Cardiovascular Parameters in Adult Growth Hormone Deficiency: Comparison Between Adult and Elderly Patients - Scarano, Elisabetta; Riccio, Enrico; Somma, Teresa; Arianna, Rossana; Romano, Fiammetta; Di Benedetto, Elea; de Alteriis, Giulia; Colao, Annamaria; Di Somma, Carolina (Frontiers in Endocrinology, 2021)
Growth hormone deficiency (GHD) in adults is due to a reduced growth hormone (GH) secretion by the anterior pituitary gland which leads to a well know syndrome characterized by decreased cognitive function and quality of life (QoL), decreased bone mineral density (BMD), increased central adiposity with a reduction in lean body mass, decreased exercise tolerance, hyperlipidemia and increased predisposition to atherogenesis. Considering some similar features between aging and GHD, it was thought that the relative GH insufficiency of the elderly person could make an important contribution to the fragility of elderly. GH stimulation tests are able to differentiate GHD in elderly patients (EGHD) from the physiological reduction of GH secretion that occurs with aging. Although there is no evidence that rhGH replacement therapy increases the risk of developing Diabetes Mellitus (DM), reducing insulin sensitivity and inducing cardiac hypertrophy, long-term monitoring is, however, also mandatory in terms of glucose metabolism and cardiovascular measurements. In our experience comparing the impact of seven years of rhGH treatment on metabolic and cardiovascular parameters in GHD patients divided in two groups (adult (AGHD) and elderly (EGHD) GHD patients), effects on body composition are evident especially in AGHD, but no in EGHD patients. The improvements in lipid profile were sustained in all groups of patients and they have a lower prevalence of dyslipidaemia than general population. The effects on glucose metabolism were conflicting, but approximately unchanged. The risk of DM type 2 is, however, probably increased in obese GHD adults with impaired glucose homeostasis at baseline, but the prevalence of DM in GHD is like general population. The increases in glucose levels, BMI and SBP in GHD negatively affected the prevalence of the MS in the long term, especially in AGHD patients. Our results are in according to other long-term studies in which effects on body composition and lipid profile are prominent.